Analisis Kesulitan Siswa Kelas VII dalam Memecahkan Masalah Matematika Materi Operasi Bentuk Aljabar - Nursafitri Amin; Muh Gazali; Fauziah Hakim (Jurnal Pendidikan Matematika : Judika Education, 2022)
This study aims to determine the difficulties of junior high school students in solving problems of operating algebraic forms. This research is included in the type of descriptive research with a qualitative approach, with the research design used is a case study. The subjects of this study were 20 students of class VII SMP Negeri 5 Sendana and 4 students were selected using a purposive sampling technique. The results of the analysis show that students' difficulties in solving algebraic operational problems consist of 4 (four) difficulty criteria, namely; 1) Able to solve problems properly and correctly; 2) Be able to understand the problem and be able to identify information on the problem, be able to plan a solution to the problem but make a mistake in implementing the problem-solving plan and re-examine the answers that have been written; 3) Difficulty understanding the problem, difficulty planning problem solving, difficulty implementing problem solving plans and difficulty re-checking answers; 4) Able to understand the problem and identify the information contained in the problem, experience difficulties in problem-solving plans, difficulties in implementing problem-solving plans and re-checking answers. In conclusion, this study resulted in an analysis of the difficulties of class VII students in solving mathematical problems material for algebraic operations in three ability categories, namely; 1) Subjects with high ability category (ST); 2) Subjects with medium ability category (SS) and 3) Subjects with low ability category (SR) Keywords: Difficulty analysis, Problem solving, Operations of Algebraic Forms